Micromorphology and bond strength evaluation of adhesive interface of a self‐adhering flowable composite resin–dentin: Effect of surface treatment. Issue 5 (26th February 2016) - Shafiei, Fereshteh; Saadat, Maryam
ABSTRACT: This study evaluated the effect of dentin surface treatment on the micromorphology and shear bond strength (SBS) of a self‐adhering flowable composite, Vertis Flow (VF). Flat dentin surfaces obtained from sixty extracted human molars were divided into six groups ( n  = 10) according to the following surface treatments: (G1) control, no treatment; (G2) self‐etching adhesive, Optibond All‐in‐One; (G3) phosphoric acid etching for 15 s; (G4) polyacrylic acid for 10 s; (G5) EDTA for 60 s; and G6) sodium hypochlorite (NaOCl) for 15 s. After restoration using VF, SBS was measured in MPa. Data were analyzed using one‐way ANOVA and Tamhane test ( α  = 0.05). Six additional specimens were prepared for scanning electron microscopy analysis. SBS was significantly affected by surface treatment ( P  < 0.001). SBS of six groups from the highest to the lowest were as follows: (G3) 13.5 A ; (G5) 8.98 AB ; (G2) 8.85 AB ; (G4) 8.21 AB ; (G1) 7.53 BC ; and (G6) 4.49 C (groups with the same superscript letter were statistically similar). Morphological analysis revealed numerous long resin tags at the adhesive interface for acid‐etched group, with a few short resin tags for the control group and small gap formation for NaOCl‐treated group. In conclusion, dentin surface treatments tested differently affected bonding performance of VF; only acid‐etching effectively improved this. Microsc. Res. Tech. 79:403–407, 2016 . © 2016 Wiley Periodicals, Inc.